STRENGTHENING ISLAMIC LITERATURE IN THE INDONESIAN ENGLISH LANGUAGE TEACHING - Dedi Irwansyah (IAIN Surakarta, 2021)
The emerging interest in using literature to teach English has not yet highlighted the significance of Islamic literature within Indonesian educational context. This article presents the portrayal of Islamic literature in English language teaching (ELT) study area and offers a possible conceptual model of integrating Islamic literature into ELT. Following a library research method, with the corpus consisting of fourteen stories and one poem derived from fifteen books, the findings of this study show that: most works of Islamic literature are designed for fluent readers; the presentation of Islamic literature is dominated by Middle East and Western writers; and the Western writers are not always sensitive to the symbols glorified by Muslim English learners in Indonesia. As to deal with the above findings, this study proposes a conceptual model consisting of input, process, and output elements. Not only does the proposed model strengthen the position of Islamic literature, but it also integrates the Islamic literature into English language teaching so that it could reach both fluent readers and beginning readers. The output of the proposed model, abridged and unabridged texts of the Islamic literature, can be utilized to teach vocabulary, grammar, the four basic skills of language, and Islamic values.Â